The Mathematical Description for Insubosin Electrochemical Detection, Assisted by coo(oh) – poly(3,4- Ethylendioxythiophene) Composite - Романів, Людмила Вікторівна (Analytical and Bioanalytical Electrochemistry, 2018)
The possibility of Insubosin electrochemical determination, assisted by CoO(OH) – Poly(3,4-ethylendioxythiophene) hybrid material has been evaluated. The correspondent mathematical model has been developed and analyzed by means of linear stability theory and bifurcation analysis. It was shown that the hybrid material may be applied as an efficient electrode modifier in the detection of Insubosin as sodium salt in neutral and lightly alkaline media. The electrochemical response has to be clear and easy to interpret. The possibility of the oscillatory and monotonic instabilities has also been verified.
Keywords: Medication safety, Insubosin, Poly(3,4-ethylendioxythiophene)s, Cobalt (III) oxyhydroxide, Electrochemical sensors, Stable steady-state